THE SOUNDS SHIFTED BY THE MYANMAR SPEAKER IN ENGLISH PRONUNCIATION: PHONOLOGICAL ANALYSIS - Ambalegin, Ambalegin; Nasir, Muhammad; Thu, Aung Si (Asosiasi dosen IDEBAHASA KEPRI, 2025)
This study is a phonological analysis that discusses the sounds of letters spoken in English words viewed from phonology and phonetics. The purpose of this study is to describe the use of sound patterns on vowels and consonants of English words. This study identifies the sound shifting produced by the Myanmar speaker. The data were collected by using observation method. The technique used was the recording and note-taking. Then, the data were analyzed by using phonetic articulatory identity method. The theories used were Roach, Fasold and Connor-Linton, Finegan, Ladefoged and Disner, and Skandera and Burleigh's theories related to the pronunciation corresponding to English phonetic symbols. Furthermore, the results of data analysis were presented by using descriptive narrative. The phonological issues occurred in term of deletion, insertion, and alteration. There were some sounds shifted and neutralized to the speaker’s first language. The effect of first language pronunciation makes the English pronunciation unstandardized.